Pain in the aaS. (Economist, 2008)
The article focuses on an unforeseen result of the trend in the computer industry for software to be available for downloading via the Internet, called "software as a service." Computer criminals are mimicking this development, creating Web sites which market malicious software for use by other criminals. This has led some legitimate companies to ban Internet-acquired software from their operations, and threatens the entire concept.